Teknik Şartnamelerin Proje Süreci İle İlişkisi Ve Şartname İndeks Sisteminin Oluşturulması - Ören, Gülşen (Fen Bilimleri Enstitüsü, 2015)
Bu çalışma kapsamında teknik şartnamelerin proje süreci ile ilişkisi incelenmiş ve bu sürecin tüm açılardan en efektif hale gelebilmesi için; oluşturulan bir indeks sistemi ile teknik şartnamelerin otomasyon sistemine geçişleri önerilmiştir. Teknik şartnamelerin inşaat dokümanlarının önemli bir bileşeni olması dolayısıyla inşaat dokümanları açıklanmış, teknik şartname çeşitleri, yazım kuralları ve teknik şartnamelerin proje süreci ile ilişkisi incelenmiştir. Türk inşaat sektöründe teknik şartname hazırlayan özel kuruluşların olmaması ve teknik şartname düzenlemeleri ile ilgili yetersizlikleri firmaların kendi içlerinde çözmeye çalışmaları, standart bir teknik şartname oluşturma ve indeks sisteminin gerekliliğini ortaya koymuştur. Önerilen şartname indeks sistemi tarzında programların uygulanmasının ve yaygınlaşmasının inşaat sektörüne büyük katkılarının olacağı düşünülmektedir.

In this thesis the interaction between the technical specifications and project process is analyzed and to make this process more effective a specification index system is suggested. The technical specifications are one of the important components of construction documents, so firstly construction documents, then technical specification kinds, grammar rules and finally contact between the technical specifications and project process are explained. In Turkish construction sector there is no specific establishment which prepares technical specifications and construction companies try to solve insufficiencies about technical specification preparation themselves. This situation indicated that standard technical specification form and index system is required. Finally it is obvious that using systems like the technical specification index system has a lot of advantages for Turkish construction sector.
Relation Between Technical Specifications And Project Process And Building Technical Specifications Index System
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2006
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2006
Keywords: Teknik Şartnameler; Sözleşme Yönetimi; Şartname İndeks Sistemi; Technical Specifications; Contract Management; Specification Index System